2008
DOI: 10.1038/nature06640
|View full text |Cite
|
Sign up to set email alerts
|

Transient cyclical methylation of promoter DNA

Abstract: Methylation of CpG dinucleotides is generally associated with epigenetic silencing of transcription and is maintained through cellular division. Multiple CpG sequences are rare in mammalian genomes, but frequently occur at the transcriptional start site of active genes, with most clusters of CpGs being hypomethylated. We reported previously that the proximal region of the trefoil factor 1 (TFF1, also known as pS2) and oestrogen receptor alpha (ERalpha) promoters could be partially methylated by treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
407
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 588 publications
(429 citation statements)
references
References 23 publications
16
407
1
5
Order By: Relevance
“…Such a process could allow for a reversal of the methylation mark by transcription factor signaling. Indeed, there is recent evidence [83,84] that both demethylation and remethylation might occur over remarkable short periods of time, reflecting a process that is, at least at certain regions of the genome, highly dynamic and closely linked to transcriptional regulation. In one exciting model [84] DNA methylation/demethylation of the cytochrome p450 27B1 (CYP27B1) gene promoter is dynamically regulated by vitamin-D-mediated transrepression, which associates with increased methylation, and parathyroid hormoneinduced activation, which associates with demethylation.…”
Section: The Epigenome: Chromatin Structure and Dna Methylationmentioning
confidence: 99%
“…Such a process could allow for a reversal of the methylation mark by transcription factor signaling. Indeed, there is recent evidence [83,84] that both demethylation and remethylation might occur over remarkable short periods of time, reflecting a process that is, at least at certain regions of the genome, highly dynamic and closely linked to transcriptional regulation. In one exciting model [84] DNA methylation/demethylation of the cytochrome p450 27B1 (CYP27B1) gene promoter is dynamically regulated by vitamin-D-mediated transrepression, which associates with increased methylation, and parathyroid hormoneinduced activation, which associates with demethylation.…”
Section: The Epigenome: Chromatin Structure and Dna Methylationmentioning
confidence: 99%
“…14,15 This important pathway for active DNA demethylation has been thought to be involved in a number of prominent biological processes. 5,6,10,11 Early and recent studies suggested that active and replication-independent DNA demethylation might be a rapid process. 10,11 The radically altered methylation, as observed in replication-independent demethylation of the paternal genome in zygotes, may complete within hours.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5,6,10,11 Early and recent studies suggested that active and replication-independent DNA demethylation might be a rapid process. 10,11 The radically altered methylation, as observed in replication-independent demethylation of the paternal genome in zygotes, may complete within hours. 5,6,17−19 However, the observed levels of the active DNA demethylation intermediates, 5fC and 5caC in the cultured cells, were 100-fold less than the primary product 5hmC.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dnmt3a and Dnmt3b are known to control non-CpG methylation [38,39]. Dnmt3a can also function as a DNA demethylase [54]. Dnmt3L is a catalytically inactive homologue of Dnmt3a and Dnmt3b that functions as an essential regulatory cofactor for tetrameric complex assembly [55].…”
Section: Mammalian Dnmts In the Central Nervous Systemmentioning
confidence: 99%